Local creation for global use in the information age: Accessing Malay indigenous information at ATMA via the portal www.malaycivilization.com - Ding, Choo Ming (Universiti Kebangsaan Malaysia, 2004)
Starting out with one database in 1999, named PADAT, there are today six databases offering a respectable array of information and materials via www.malaycivilization.com. These databases are continuously expanded with the objective of broadening and deepening research on Malay world studies during a time when the increasing use of IT and its widespread acceptance among researchers have not only brought massive changes to scholarly research and communication, but also affected the very survival of research institutes themselves. In this context, we place great value and trust in science and technology, believing that IT and Internet hold immense possibilities to facilitate research through ‘one-to-many’, ‘many-to-one’ and ‘many-to-many’ communication. This represents a paradigm shift from the conventional blanket collection development practised in libraries throughout the world. In this information age, sustainable competitive advantage is no longer based on technology alone, but also on the accessibility of information and materials. This paper is divided into three parts. First, we have a condensed definition of Malay indigenous information, followed by a section on the ATMA’s strategies and efforts to create one database after another to increase the diversity of materials relating to Malay world studies. We concluded with our diversification plan to make these projects self-financing and self-sustaining for a foreseeable future